Stock structure of blue threadfin Eleutheronema tetradactylum across northern Australia, as indicated by parasites - Moore, B.; Stapley, J.; Allsop, Q.; Newman, Stephen; Ballagh, A.; Welch, D.; Lester, R. (Wiley-Blackwell Publishing Ltd., 2011)
The parasite fauna of the blue threadfin Eleutheronema tetradactylum, collected from 14 sites across northern Australia, was examined to evaluate the degree of movement and subsequent stock structure of the fish. Univariate and multivariate analysis of nine 'permanent' parasite species [the nematodes Anisakis (type I) and Terranova (type II), the cestodes Otobothrium australe, Pterobothrium pearsoni, Pterobothrium sp. A, Callitetrarhynchus gracilis, Parotobothrium balli and Nybelinia sp., and the acanthocephalan Pomphorhynchus sp.] demonstrated little similarity between sites, indicating limited mixing and therefore long-term separation of post-juvenile fish. As such, the effects of fishing are likely to be localized within the current administrative boundaries, implying little need for interstate co-operative management. Within each jurisdiction, management of E. tetradactylum populations, including the establishment of harvest strategies and fishery regulations, should be conducted in a way that recognizes the resident nature of the fish. © 2011 The Authors. Journal of Fish Biology © 2011 The Fisheries Society of the British Isles.